Pengaruh Struktur Modal dan Ukuran Perusahaan terhadap Profitabilitas pada Perusahaan Food & Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2010-2015 - Fitri Astuti; Muhammad Roni Indarto (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
This study aims to explain the influence of the variable capital structure and firm size on profitability. This study uses secondary data taken from the Indonesia Stock Exchange in the Manufacturing sector, Food and Beverage sub-sector in the period 2010 - 2015. The data analysis techniques used are basic assumption tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the results of the analysis that has been described, it can be concluded that the DER variable with a significance value of 0.0042 is less than 0.05. accept the initial hypothesis H0. Total assets with a significance value of 0.0000 less than 0.05. reject the initial hypothesis, and accept the alternative hypothesis Ha2 is accepted.